Hemingway's laboratory : the Paris in our time - Cohen, Milton A. (University of Alabama Press, 2012)
Illuminates the development of Hemingway's themes and techniques and his future course as a stylist and writer. In 1924 Ernest Hemingway published a small book of eighteen vignettes, each little more than one page long, with a small press in Paris. Titled in our time, the volume was later absorbed into Hemingway's story collection In Our Time. Those vignettes, as Milton Cohen demonstrates in Hemingway's Laboratory, reveal a range of voices, narrative strategies, and fictional interests more wide-ranging and experimental than any other extant work of Hemingway's. Furth.